Nanotechnology and Osteoarthritis. Part 2: Opportunities for advanced devices and therapeutics. Issue 3 (22nd September 2020) - Lawson, Taylor B.; Mäkelä, Janne T. A.; Klein, Travis; Snyder, Brian D.; Grinstaff, Mark W.
Abstract: Osteoarthritis (OA) is a multifactorial disease of the entire joint which afflicts 140 million individuals worldwide regardless of economic or social status. Current clinical treatments for OA primarily center on reducing pain and increasing mobility, and there are limited therapeutic interventions to restore degraded cartilage or slow disease pathogenesis. This second installment of a two‐part review on nanotechnology and OA focuses on novel treatment strategies. Specifically, Part 2 first discusses current surgical and nonsurgical treatments for OA and then summarizes recent advancements in nanotechnology‐based treatments, while Part 1 (10.1002/jor.24817) described advances in imaging and diagnostics. We review nano delivery systems for small molecule drugs, nucleic acids, and proteins followed by nano‐based scaffolds for neocartilage formation and osteochondral regeneration, and lastly nanoparticle lubricants. We conclude by identifying opportunities for nanomedicine advances, and prospects for OA treatments.